Implementasi Model Pendidikan Karakter Melalui Pendidikan Agama Islam di SMAN 2 Ks Kota Cilegon Provinsi Banten - Suaidi Suaidi (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This paper presents the results of research on the implementation of the model for implementing character education in high schools with the case at SMAN 2 KS Cilegon City, Banten Province. the school components and Islamic religious education teachers are the main actors, with the support of conducive policies from the principal of SMAN 2 KS Cilegon City, Banten Province. The presence and involvement of campus activists through monitoring requires scrutiny and coordination that is integrated with the Islamic religious education teacher program.